The Effect of Manager's Role on Manpower Training and their Implementation on Capital Investment Collection (Case Study on MSMEs Assisted by the West Java Chamber of Commerce) - R Susanto Hendiarto; Vera Ferrisa (Institute of Computer Science (IOCS), 2022)
The current problem of raising capital investment is still far from expectations, while labor training has not been encouraging, this is presumably because the role of managers is still apprehensive. This study aims to determine the effect of the manager's role on labor training and labor training on capital investment accumulation, which is applied in the form of a descriptive analytical survey method, while the sample used is 39 respondents. The variables studied from each respondent are the role of managers, labor training and capital investment collection. The type of data collected is primary data. The results of the study indicate that the role of the manager has no and no significant effect on the training of the workforce. manpower training has no effect and is not significant to the accumulation of capital investment. The implication is that the role of managers needs to be intensified within the organization. The object of this research is the sample of respondents used is still limited to the business assisted by the West Java Chamber of Commerce in Bandung, therefore further research is necessary based on more varied sampling with a longer duration, in order to obtain generalizable results.